Gambaran Peresepan Antibiotik di Poli Telinga Hidung Tenggorokan (THT) di Rumah Sakit X Kabupaten Situbondo - Syah, Farid Zulkarnain Nur; Nanda, Solikhati Ika (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Antibiotics are chemical compounds used to treat bacterial infections by inhibiting the growth or killing bacteria. Antibiotics are classified as prescription medications, meaning their use must be based on a doctor's recommendation and prescription. The selection of antibiotics should be based on information about the spectrum of microorganisms causing the infection, microbiological test results, pharmacokinetic and pharmacodynamic profiles of the antibiotics, as well as their affordability. The prescribing of antibiotics in hospitals, both in terms of the types of antibiotics used and the medical reasons for their use, may vary depending on the guidelines for antibiotic use at each hospital. This study aims to provide an overview of antibiotic prescribing in the Ear, Nose, and Throat (ENT) clinic at Situbondo District Hospital. The research design is descriptive observational. The samples used were all doctor prescriptions from the ENT clinic at the hospital, filled at the outpatient pharmacy depot during November 2023. The sampling technique employed was total sampling, resulting in 110 prescriptions. The findings showed that the most commonly prescribed antibiotics were Co-Amoxiclav (66.2%), Cefixime (20.0%), Levofloxacin (7.6%), Azithromycin (4.1%), and a combination of Polymyxin B Sulfate and Neomycin Sulfate (2.1%). Regarding the duration of antibiotic therapy, oral antibiotics were prescribed for 2 to 7 days, while ear drops were used for 20 to 27 days.